PENGARUH KERUSAKAN DAN KELERENGAN JALAN HUTAN TERHADAP PRODUKTIVITAS PENGANGKUTAN KAYU STUDI KASUS DI KALIMANTAN BARAT - S Sutopo; Rahardjo S Suparto (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Timber transportation productivity decreases when forest road is deteriorated and the 8lope is large. This study tried to investigate the effect of slope and road damage on timber transportation productivity, and was carried out at the PT Sari Bumi Kusuma forest company areas in West Kalimantan in 1987.The investigation results are as follows:Slope difference of 5% has significant effect on transportation productivity. On flat, medium and steep slopes, the productivities are 265, 219 and 132 m3. km/hr, respectively.Transportation productivity is significantly influenced by a difference of 15% damage on the road. Productivities on relatively good road, medium damaged and badly damaged roads are 292,213 and 136 m3.km/hr, respectively.On flat and badly damaged roads (at a damage level greater than 30%), transportation productivity is reduced 64% which caused significant financial loss. The allowable road damage on (at terrain without causing financial loss is 40%.On medium terrain and medium damaged roads (at damage levels between 15% and 30%), the loss is significant. Medium damaged (between 15% and 30%) and heavy damaged roads (greater than 30%) caused transportation productivities to be decreased as much as 25% and 58%, respectively, The allowable road damage on medium terrain without causing financial loss is 26%.On steep terrain, transportation productivity is decreased significantly i.e. 58% of those on medium damaged roads (between 15% and 30%). A maximum road damage of 18% is allowable without causing financial loss.There is a significanf interaction between slope and road damage. The steeper the slope and the heavier the road damage, the larger the decrease in transportation productivity.In the transportation distance of 60 km and the timber price of US 70/m3, if timber transportation productivity decreases 30%, it is strongly suggested to repair damaged road immediatly in order to prevent financial losses.